International intellectual property after the new NAFTA - Jeremy De Beer (Centre for International Governance Innovation (CIGI), 2020)
The Canada-United States-Mexico Agreement (CUSMA) is the new high-water mark in international intellectual property (IP) law. CUSMA includes most of the Trans-Pacific Partnership provisions that were suspended in the Comprehensive and Progressive Trans-Pacific Partnership, except for a few pharmaceutical-related provisions amended after signing. Canada will be required to make meaningful changes to domestic IP laws, including copyright term extension, criminal penalties for tampering with digital rights management information, restoration of patent terms to compensate for administrative and regulatory delays, broader and longer protection for undisclosed testing data and other data, new civil and criminal remedies for the misappropriation of trade secrets, and additional powers for customs officials to seize and destroy IP-infringing goods.
Keywords: 330; Intellectual Property Rights; International Right; FTA; USMCA States; Immaterialgüterrechte; Internationales Recht; Freihandelsabkommen; USMCA-Staaten